Endoplasmic reticulum stress‐mediated autophagy protects against β, β‐dimethylacrylshikonin‐induced apoptosis in lung adenocarcinoma cells. Issue 6 (19th May 2018) - Wang, Haibing; Zhang, Gaochenxi
Abstract : β, β‐Dimethylacrylshikonin (DMAS) is an anti‐cancer compound extracted from the roots of Lithospermum erythrorhizon . The present study aims to investigate the effects of DMAS on human lung adenocarcinoma cells in vitro and explore the mechanisms of its anti‐cancer action. We showed that DMAS markedly inhibited cell viability in a dose‐ and time‐dependent way, and induced apoptosis as well as autophagy in human lung adenocarcinoma cells. Furthermore, we found that DMAS stimulated endoplasmic reticulum stress and mediated autophagy through the PERK‐eIF2α‐ATF4‐CHOP and IRE1‐TRAF2‐JNK axes of the unfolded protein response in human lung adenocarcinoma cells. We also showed that the autophagy induced by DMAS played a prosurvival role in human lung adenocarcinoma cells and attenuated the apoptotic cascade. Collectively, combined treatment of DMAS and pharmacological autophagy inhibitors could offer an effective therapeutic strategy for lung adenocarcinoma treatment. Abstract : DMAS inhibits cell viability, and induces apoptosis as well as autophagy. DMAS induces autophagy through the activation of endoplasmic reticulum stress response. Autophagy induced by DMAS plays a prosurvival role and attenuates the apoptotic cascade.